Effects of supplementation of probiotics instead of antibiotics to broiler diet on growth performance, nutrient retention, and cecal microbiology - Rahman, Md Mustafijur; Khan, Mohammad Mehedi Hasan; Howlader, Md Matiar Rahman (Journal of Advanced Veterinary and Animal Research, 2021)
Objectives: The research was carried out on broilers to determine the efficacy of probiotics (Bacillus subtilis and Saccharomyces boulardii combined) supplementation on growth performances, nutrient retention (metabolizable energy, dry matter, and crude protein), and cecal microbiology (Bifidobacteria spp., Clostridium spp., and coliforms). Materials and Methods: A total of 160 broiler chicks (day-old) were selected and differentiated randomly into 4 groups (T0, T1, T2, and T3) (40 × 4) comprising 40 birds in every single group. The control group (T0) was fed commercial broiler feed only and the other three groups, referred to as treatment groups (T1, T2, and T3), were treated with 1 gm ciprofloxacin, 1 gm probiotic, and 1 gm probiotic plus 0.5 gm enzyme, respectively, in per liter of fresh dietary water 8 h daily for 7 days in each phase. Experimental trials were divided into 2 phases, the starter phase from day 0 to 21 and the finisher phase from day 22 to 35. Results: Bodyweight gain and nutrient retention in experimental broiler birds in treatment groups were significantly (p < 0.05) higher than the control group. Overall body weight gain and nutrient retention of broiler chicks in treatment groups T2 and T3 were better than T1. From day 22 to 35, cecal Clostridium and coliform bacterial load counts were significantly lower p < 0.01, p < 0.05, and p < 0.01, respectively, in T1, T2, and T3 treatments than T0. Overall, Clostridium and coliform bacterial counts in the birds of treatment group T2 were significantly lower (p < 0.05) than T0. Conclusion: The probiotics, in addition to enzyme supplementation, had suitable influence effects on growth performance of broilers, birds retention of nutrient, and microfloral count in birds’ cecum. J. Adv. Vet. Anim. Res., 8(4): 534-539, December 2021 http://doi.org/10.5455/javar.2021.h543